Insights into the Silver Camphorimine Complexes Interactions with DNA Based on Cyclic Voltammetry and Docking Studies - Joana P. Costa; Gonçalo C. Justino; Fernanda Marques; M. Fernanda N. N. Carvalho (Molecules)
Cyclic voltammetry (CV) is an accessible, readily available, non-expensive technique that can be used to search for the interaction of compounds with DNA and detect the strongest DNA-binding from a set of compounds, therefore allowing for the optimization of the number of cytotoxicity assays. Focusing on this electrochemical approach, the study of twenty-seven camphorimine silver complexes of six different families was performed aiming at detecting interactions with calf thymus DNA (CT-DNA). All of the complexes display at least two cathodic waves attributed respectively to the Ag(I)→Ag(0) (higher potential) and ligand based (lower potential) reductions. In the presence of CT-DNA, a negative shift in the potential of the Ag(I)→Ag(0) reduction was observed in all cases. Additional changes in the potential of the waves, attributed to the ligand-based reduction, were also observed. The formation of a light grey product adherent to the Pt electrode in the case of {Ag(OH)} and {Ag2(µ-O)} complexes further corroborates the interaction of the complexes with CT-DNA detected by CV. The morphologic analysis of the light grey material was made by scanning electronic microscopy (SEM). The magnitude of the shift in the potential of the Ag(I)→Ag(0) reduction in the presence of CT-DNA differs among the families of the complexes. The complexes based on {Ag(NO3)} exhibit higher potential shifts than those based on {Ag(OH)}, while the characteristics of the ligand (AL-Y, BL-Y, CL-Z) and the imine substituents (Y,Z) fine-tune the potential shifts. The energy values calculated by docking corroborate the tendency in the magnitude of the interaction between the complexes and CT-DNA established by the reaction coefficient ratios (Q[Ag-DNA]/Q[Ag]). The molecular docking study extended the information regarding the type of interaction beyond the usual intercalation, groove binding, or electrostatic modes that are typically reported, allowing a finer understanding of the non-covalent interactions involved. The rationalization of the CV and cytotoxicity data for the Ag(I) camphorimine complexes support a direct relationship between the shifts in the potential and the cytotoxic activities of the complexes, aiding the decision on whether the cytotoxicity of a complex from a family is worthy of evaluation.